Evaluation of the potential effects of AS03-adjuvanted A(H1N1)pdm09 vaccine administration on the central nervous system of non-primed and A(H1N1)pdm09-primed cotton rats. Issue 1 (2nd January 2017) - Planty, Camille; Mallett, Corey P.; Yim, Kevin; Blanco, Jorge C. G.; Boukhvalova, Marina; March, Thomas; van der Most, Robbert; Destexhe, Eric
ABSTRACT: An increased risk of narcolepsy following administration of an AS03-adjuvanted A(H1N1)pdm09 pandemic influenza vaccine ( Pandemrix ™) was described in children and adolescents in certain European countries. We investigated the potential effects of administration of the AS03-adjuvanted vaccine, non-adjuvanted vaccine antigen and AS03 Adjuvant System alone, on the central nervous system (CNS) in one-month-old cotton rats. Naïve or A(H1N1)pdm09 virus-primed animals received 2 or 3 intramuscular injections, respectively, of test article or saline at 2-week intervals. Parameters related to systemic inflammation (hematology, serum IL-6/IFN-γ/TNF-α) were assessed. Potential effects on the CNS were investigated by histopathological evaluation of brain sections stained with hematoxylin-and-eosin, or by immunohistochemical staining of microglia, using Iba1 and CD68 as markers for microglia identification/activation, albumin as indicator of vascular leakage, and hypocretin. We also determined cerebrospinal fluid (CSF) hypocretin levels and hemagglutination-inhibiting antibody titers. Immunogenicity of the AS03-adjuvanted A(H1N1)pdm09 pandemic influenza vaccine was confirmed by the induction of hemagglutination-inhibiting antibodies. Both AS03-adjuvanted vaccine and AS03 alone activated transient innate (neutrophils/eosinophils) immune responses. No serum cytokines were detected. CNS analyses revealed neither microglia activation nor inflammatory cellular infiltrates in the brain. No differences between treatment groups were detected for albumin extravascular leakage, CSF hypocretin levels, numbers of hypocretin-positive neuronal bodies or distributions of hypocretin-positive axonal/dendritic projections. Consequently, there was no evidence that intramuscular administration of the test articles promoted inflammation or damage in the CNS, or blood-brain barrier disruption, in this model.